... Rethinking State Theory Gramsci and Contemporary - Dharma Prasetyo, Dwi; Sinaga, Jona Bungaran Basuki; Soleh, Mohamad; Haekal, Muhammad (Institute of Computer Science (IOCS), 2025)
One of the most significant aspects of Antonio Gramsci’s social theory is his analysis of political strategy, particularly his distinction between